Deformation Coupled Effective Permeability Change in Hydrate-Bearing Sediment during Depressurization - Xiang Sun; Hao Luo; Kenichi Soga (Processes, 2022)
Methane hydrates found in the sediments of deep sea and permafrost regions draw global interest. The rate of gas production from a depressurized well is governed by the effective permeability of the hydrate-bearing sediments around the wellbore. During depressurization, a decrease in pore pressure leading to soil compaction and hydrate dissociation results in a dynamic change in the effective permeability. To describe the change in the effective permeability in detail, in this study, a simple coupled compressibility–permeability analysis method is proposed to identify the conditions under which the effective permeability increases or decreases after depressurization. An analytical solution is derived for the effective permeability change with pore pressure and temperature, considering hydrate dissociation and soil compaction. We found that when there is a sufficient heat supply, hydrate dissociation dominates the effective permeability during hydrate dissociation, but after hydrate dissociation, soil compaction is the governing factor for permeability change. When there is an insufficient heat supply, however, compaction mainly determines the permeability, and the effect of hydrate dissociation is limited. This work will be helpful for rapid reservoir assessment.